Fenomena Mengemis Online: Analisis Perspektif Hadis tentang Etika Kerja dan Larangan Mengemis - Alis, Fijrah Hayati; Samad, Duski; Mamad, Firdaus Sutan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
The development of digital technology has given rise to a new phenomenon in the form of online begging practices through live streaming and giving gifts on social media. This activity is often carried out by displaying acts of humiliation or exploiting certain conditions in order to gain public sympathy, thus having an impact on weakening work ethics and economic independence of the community. From an Islamic perspective, work is a form of maintaining dignity, and the hadith emphasizes the virtue of giving rather than asking without urgent need. This study aims to describe the phenomenon of online begging, analyze the hadith about the prohibition of begging and the encouragement of independence, and explain its relevance to digital ethics. This research uses a qualitative approach with library research. The results of this study found that the phenomenon of online begging is not in accordance with Islamic work ethics. In the Islamic perspective, work is a noble activity and is part of worship, while begging without urgent need is a despicable act that damages one's honor. The Prophet's hadiths encourage Muslims to be productive, independent, and self-reliant. As stated in the hadith about the priority of the hands above is better than the hands below.